Pengaruh Transparansi Dan Akuntabilitas Terhadap Kepercayaan Peserta Pada PT. TASPEN (Persero) Cabang Mataram - Nadia Setiawati; Rossi Maunofa Widayat; Nurul Hidayati Indra Ningsih; Sulhan Hadi (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2025)
This study aims to analyze the influence of transparency and accountability on participants' trust at PT TASPEN (Persero) Mataram Branch Office. The background of this research is based on the importance of transparency and accountability in building trust among participants as beneficiaries of pension and social insurance services. A quantitative research method was employed, with data collected through questionnaires distributed to 60 respondents who are service participants at PT TASPEN (Persero) Mataram Branch Office. Data analysis was conducted using validity and reliability tests, classical assumption tests, and multiple linear regression analysis with the assistance of SPSS software. The results indicate that transparency has a significant partial effect on participants' trust. Similarly, accountability also has a significant partial effect on participants' trust. Simultaneously, transparency and accountability have a significant influence on participants' trust. These findings suggest that transparency and accountability play a vital role in building and enhancing participants' trust in the services provided by PT TASPEN (Persero) Mataram Branch Office.